Sensory Augmentation for the Blind - Kärcher, Silke M.; Fenzlaff, Sandra; Hartmann, Daniela; Nagel, Saskia K.; König, Peter (Frontiers in Human Neuroscience, 2012)
Common navigational aids used by blind travelers during large-scale navigation divert attention away from important cues of the immediate environment (i.e., approaching vehicles). Sensory augmentation devices, relying on principles similar to those at work in sensory substitution, can potentially bypass the bottleneck of attention through sub-cognitive implementation of a set of rules coupling motor actions with sensory stimulation. We provide a late blind subject with a vibrotactile belt that continually signals the direction of magnetic north. The subject completed a set of behavioral tests before and after an extended training period. The tests were complemented by questionnaires and interviews. This newly supplied information improved performance on different time scales. In a pointing task we demonstrate an instant improvement of performance based on the signal provided by the device. Furthermore, the signal was helpful in relevant daily tasks, often complicated for the blind, such as keeping a direction over longer distances or taking shortcuts in familiar environments. A homing task with an additional attentional load demonstrated a significant improvement after training. The subject found the directional information highly expedient for the adjustment of his inner maps of familiar environments and describes an increase in his feeling of security when exploring unfamiliar environments with the belt. The results give evidence for a firm integration of the newly supplied signals into the behavior of this late blind subject with better navigational performance and more courageous behavior in unfamiliar environments. Most importantly, the complementary information provided by the belt lead to a positive emotional impact with enhanced feeling of security. The present experimental approach demonstrates the positive potential of sensory augmentation devices for the help of handicapped people.